Low valent carbonylvanadium complexes of the triphosphorus macrocycle 12[ane]P3Et3. - BAKER, ROBERT (My University, 2003)
The triphosphorus macrocycle 1,5,9-triethyl-1,5,9-triphosphacyclododecane, 12[ane]P3Et3, reacts with [V(CO)6]− under photolytic conditions to produce fac-[(12[ane]P3Et3)V(CO)3]− (1) which has been isolated as its Et4N salt. This can be oxidised to the neutral 17 electron complex fac-(12[ane]P3Et3)V(CO)3 (2), which has been characterised by EPR spectroscopy. Density functional calculations support the spectroscopic observations and give insight into the bonding. The V(0) compound cannot be further oxidised, but the macrocycle reacts with CpV(CO)4 thermally or photolytically to produce cis-[(η2-12[ane]P3Et3)V(η5-Cp)(CO)2] (3). The diamagnetic compounds have been characterised by IR and multinuclear (1H, 13C, 31P and 51V) NMR spectroscopy.
PUBLISHED
Keywords: Chemistry